PENERAPAN MODEL PEMBELAJARAN COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) BERBASIS KURIKULUM BERBASIS CINTA - Sularmi Sularmi; Deni Erawati Santoso; Wati Rahayu; Emi Sulistyowati; Maya Kurnia Sari; Haryani Haryani (JURNAL ILMIAH NUSANTARA, 2026)
This study aims to examine the implementation of the Cooperative Integrated Reading and Composition (CIRC) learning model based on the Love-Based Curriculum (KBC). The main focus of the study is to analyze the role of teachers in integrating KBC values ​​and students' responses to the implementation of this model. The research findings indicate that CIRC is able to increase student engagement cognitively, socially, and emotionally. Although there are variations in implementation in each madrasah, the principles of cooperation, mutual respect, and empathy are successfully internalized in learning activities. The role of teachers as facilitators and social mediators has proven crucial in creating a learning climate that supports the internalization of love values. The main challenges faced are teachers' pedagogical readiness and time constraints that affect the comprehensive implementation of CIRC. This study makes an important contribution to the development of educational practices by emphasizing the importance of cooperative learning that integrates academic and socio-emotional aspects.